An SDS-NaOH-based method to isolate genome of recombinant adeno-associated virus vectors for physical titer measurement. - Xiangying Zhu; Keying Yang; Jinyan Xie; Xilin Feng; Tao Wu; Mengjun Hu; Haijian Wang; Chenghui Yu; Xiaomin Yu; Farhid Hemmatzadeh; Liqing Zhu; Linhua Zhang (PLoS ONE)
Recombinant adeno-associated viruses (rAAVs) vectors are promising for their safety and sustained expression of genetic payloads across various tissues. These vectors consist of a protein capsid enclosing a 4.7 kb single-stranded DNA genome. Rapid and accurate determination of the physical titers of rAAV vector is crucial for quality control in rAAV manufacturing and precise drug dosage in clinical trials. To prepare vector DNA for genome titer assessment, it is essential to completely degrade unencapsulated DNA and dissociate the capsid. Conventional methods typically involve co-incubation with DNase I to degrade unencapsidated DNA, followed by co-incubation with Proteinase K to cleave protein shells. Here, we present a "Benzonase & SDS-NaOH" pretreatment as an effective alkaline lysis for releasing the vector DNA. In the presence of producer cell crude extract, Benzonase demonstrated superior efficacy in degrading unencapsidated DNA compared to DNase I. Additionally, the use of SDS-NaOH, effective at 65 °C for 30 min, significantly reduces the time required compared to that of Proteinase K at 56 °C for 2 hours. We also showed that the "Benzonase & SDS-NaOH" pretreatment is applicable for vector genome titration in rAAV production, harvest, and purified stock. Moreover, our method is effective for both scAAV and ssAAV forms and across all serotypes, including the thermally stable rAAV5. Overall, this method offers a rapid and straightforward solution to determine rAAV vector genome titers in both purified preparations and during the manufacturing process.